(untitled) (Revista Kriterion, 2021)
In this paper, I argue that Plotinus’s critique of divine deliberation in Ennead VI.7 does not seek to banish teleology altogether from his philosophy of nature. Rather, his critique aims to situate teleology within his own metaphysical system so as to reconcile it with the basic principles governing the intelligible universe. In this sense, Plotinus does not propose that we expunge all reference to notions of utility and benefit from our natural explanations; he merely wishes to render those notions coherent with an ontology in which the intelligible always takes precedence over sensible reality. To this end, Plotinus introduces, first, what I call a vertical teleology, where the different animal species create the necessary conditions for the maintenance of higher forms of intelligible life, such as genera. Second, Plotinus advances what I call a horizontal teleology, where the various animal organs serve to provide a minimal coefficient of noetic content to each species in its respective ontic level. Plotinus thus sketches the outlines of a properly ‘noetic’ teleology in Ennead VI.7.